Evaluation of an Organic Package of Practice Towards Green Gram Cultivation and Assessment of its Effectiveness in Terms of Crop Sustainability and Soil Quality Development - Antara Seal; Ranjan Bera; Rupkatha Roy Chowdhury; Koushik Mukhopadhyay; Sudipta Mukherjee; Ajit Kumar Dolui (Turkish Journal of Agriculture: Food Science and Technology)
Restoration of soil has been identified as the option; to ensure crop sustainability. However, as per Trophobiosis Theory of French Scientist F. Chaboussou, focus on development of healthy plants is necessary to abate pest and disease invasion so as to ensure sustained crop performance, even under unfavorable environmental conditions. The present study, in randomized block design with green gram as test crop; was undertaken in Krishi Vigyan Kendra (Howrah, West Bengal) to evaluate the effectiveness of Inhana Rational Farming (IRF) Technology towards crop yield and soil quality development under different sustainable models viz. organic cultivation, integrated soil with organic crop management and non- chemical crop management; as compared to conventional farming practice. Highest yield was recorded under organic (933 kg ha-1) followed by integrated (921 kg ha-1) and non- chemical plant management (902 kg ha-1). The results were well corroborated with the plant development index obtained under these treatments. Favorable trend of soil quality under sustainable models especially in terms of microbial properties indicated the role of quality compost towards speedy rejuvenation of soil dynamics. The study indicated that reduction of synthetic fertilizers and qualitative management of soil is essential to restrict yield decline. However, plant management shall be prerequisite for ensuring crop sustainability without any time lag and under the changing climatic patterns. In this respect the potential of IRF Technology has been well accounted.